Jerusalem [videorecording] within these walls - Birch, Miriam; Kane, Dennis B.; Skinner, Thomas (National Geographic Society special, 1986)
Explores the historic old city that is sacred for three major religions. Studies the cultural roots and the clash of ancient and modern forces.